1982
DOI: 10.1080/00039896.1982.10667572
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cigarette Smoking and Age on Bone Loss in Men

Abstract: Hand X-rays were examined among 341 healthy male participants (age 40-80 yr) of the Normative Aging Study who had two successive X-rays 3 to 5 yr apart. Bone density was estimated at midshaft of the second metacarpal as percent cortical area. As expected, cross-sectional analysis revealed a decrease in percent cortical area with age. Current smokers tended to have slightly lower percent cortical areas than "never" smokers. When participants were followed longitudinally over a 3 to 5 year period, a trend toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In 341 male subjects aged between 40-80 yrs smoking added to the bone loss due to ageing [21]. In this wide range of ages, the current smokers had a lower per cent of bone cortical areas than those who never smoked.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In 341 male subjects aged between 40-80 yrs smoking added to the bone loss due to ageing [21]. In this wide range of ages, the current smokers had a lower per cent of bone cortical areas than those who never smoked.…”
Section: Epidemiologymentioning
confidence: 99%
“…In this wide range of ages, the current smokers had a lower per cent of bone cortical areas than those who never smoked. In a multiple regression analysis, after adjustment for the initial percentage of cortical area, both age (p=0.005) and smoking (p=0.03) were inversely related to the per cent cortical area [21].…”
Section: Epidemiologymentioning
confidence: 99%
“…Excess ethanol intake may cause osteoporosis (5-7) by directly inhibiting osteoblast function and bone formation (8-1 1). Tobacco use has also been reported to have deleterious effects on bone mass (5,12,13) and osteoblast activity (8). Although studies on trabecular bone formation using dynamic bone histomorphometry have indicated that the recruitment and activity of osteoblasts may be altered in men with idiopathic osteoporosis (8,11,14), the cellular osteoblastic dysfunction responsible for the defective bone formation in these patients remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Potential reasons for these differences include variations in bone sites examined and methods of bone density measurement, end points of interest, age and menopausal status of subjects, source of subjects, and adjustment for confounding variables. In addition, most studies ofbone density have been conducted only in women, and most have not examined the hip, the site of most serious fractures in the elderly.…”
Section: Introductionmentioning
confidence: 99%